Threat of Ecological Destruction in Home-Based Batik Production: a Narrative of Protecting Domestic Sphere - Arianti Ina Restiani Hunga (Yayasan Jurnal Perempuan, 2014)
Shifting the location of Batik production from factory to home has manipulated the livelihood of domestic arena and its livelihood. This has deteriorated the ecological support of the house by its chemical-based batik pollutants. It then created problems such as diseases, clean water scarcity and problems of pollution, air pollution, and the consumption of drug to boost their stamina in producing Batik. The economic cost is also another burden since the production cost such as water, electricity, and space are not the responsibility of the boss but the home workers. The health and social cost is high and creating multiple ecological, psychological, and social impairments. The previous problem has enacted many women to create eco-friendly batik production.